ANALISIS KUALITAS PRODUK DAN CITRA MEREK DALAM MEMPENGARUHI KEPUTUSAN PEMBELIAN DAN DAMPAKNYA TERHADAP LOYALITAS MEREK HP NOKIA - Tjahjaningsih, Endang; Yuliani, Maurine (Jurnal Ilmiah Telaah Manajemen, 2009)
This research aims to develop and test empirical model of development brand loyalty on the basis of product quality and brand image. The research was conducted at customer of Handphone brand of Nokia . The empirical test model used was regression analysis by using some software, such as: SPSS 13.0 and Microsoft Excel version. 2007. The sample size of the study was 100 customer of Handphone brand of Nokia in Semarang. The results showed that product quality affect positively towards decision of purchasing, and brand image affect positively towards decision of purchasing. Quality product, brand image, and decision of purchasing affect positively towards brand loyality. Furthermore, product quality have indirect effect to brand loyalty through mediating decision of purchasing, product quality have direct effect to brandloyalty so that total effect product quality to brand loyalty is equal to effect indirect plus effect direct. Brand image have indirect effect to brand loyalty through mediating decision of purchasing.Keywords: Product quality, brand image, decision of purchasing, and brand loyalty.